(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the multifaceted role of intonation in English, emphasizing its importance in communication. It highlights six key functions: indicating sentence types, expressing emotions and attitudes, structuring speech, emphasizing new information, managing turn-taking in conversations, and conveying subtle nuances. The article underscores how intonation shapes meaning beyond words, providing emotional depth and clarity in spoken interactions. It also stresses the importance of mastering intonation, particularly for language learners, to enhance fluency and understanding. Through its analysis, the article demonstrates that intonation is an indispensable element of effective and meaningful communication.